Communication needs and information in the cancer survivor - Maté, Jorge; Navarro, Elsa; Limonero, Joaquin T.; Gómez-Romero, María José (Psicooncología, 2010)
Aim. The main aim of this article is to know whether cancer survivor patients have different communication and information needs in contrast to cancer patients in other stages of the disease. Method. A questionnaire was designed to assess the frequency and importance of 15 doctor-patient situations related to informational and communicational aspects. Information about the most important situations to patients is achieved too. The questionnaire was administered to patients in control sessions by means of a semi-structured interview. Results. The sample of this study is made up of 85 patients (30 cancer survivors patients and 55 cancer patients in other phase of illness). Generally, the score obtained in frequency is smaller than the score given in importance by participants to the same situations. More exactly, cancer survivor patients consider most important the situations proposed in contrast to cancer patients in other stages. Nevertheless, both sorts of patients choose the informational aspects of the communication, as the most important, in contrast to emotional aspects. Conclusion. The results show the need to provide survivor cancer patients with continuous, specialized and patient-centered care that could help them to cope with biopsychosocial problems derived from the disease.
Keywords: Communication; Doctor-patient relationship; Oncology communication; Cancer survivor